RETRACTED: Analysis of Fiscal Gaps and Regional Transfers Between Regions in Indonesia - Andri Ardiansyah; Florensius Goo; Kumba Digdowiseiso (Journal of Social Science, 2024)
This research aims to analyze fiscal gaps and regional transfers between regions in Indonesia within the framework of the fiscal decentralization policy implemented by the Indonesian government. The research method uses a qualitative descriptive research type using literature studies based on secondary data. The results of the research show that the fiscal gap and regional transfers between regions in Indonesia are a form of the failure of transfer funds between regions in Indonesia to significantly reduce economic inequality and public services between regions, which are also thought to be influenced by factors in regional financial management and resource allocation that are not yet efficient and effective. Even though transfer funds have been distributed to areas outside Java-Bali, if the management is not efficient and effective, the limited amount of funds will certainly not be able to catch up with the region. This condition is influenced by the implementation of centralized policies in Indonesia, which have proven to cause high regional dependence on the center. This dependence can be seen from the large contribution from the center, which far exceeds revenues from PAD. As a result of the centralized budget policy pattern at the center, high vertical fiscal inequality occurs.